Consider an arithmetic progression of terms such that:
Calculate the value of .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let a be the first term, a 2 be the second term, a n − 1 be the ( n − 1 ) th term, a n be the n th term and S n be the sum of all terms of this arithmetic progression.
a + a n − 1 = 9 9 1 ⟶ 1 a 2 + a n = 1 0 0 5 ⟶ 2
Adding 1 and 2 , we get:-
a + a n − 1 + a 2 + a n = 1 9 9 6 2 ( a + a n ) = 1 9 9 6
Because, sum of terms equidistant from the beginning and ending of an arithmetic progression are equal.
a + a n = 9 9 8 ⟶ 3 .
S n = 2 n × ( a + a n ) 7 1 3 5 7 = 2 n × 9 9 8 ( From 3 ) 9 9 8 7 1 3 5 7 × 2 = n n = 1 4 3